Potential of Adding Constructed Wetland/Fishpond to Waste Stabilization Ponds to Improve Helminths Removal in Morogoro Municipality, Tanzania - A.H. Outwater; A. Zachariah; A. Nyomora; F. Francis; J.H.Y. Katima (Journal of Applied Sciences and Environmental Management)
A study was conducted to establish the potential of constructed wetlands in Morogoro Urban District, Tanzania, to remove helminths from wastewater. The standard wastewater treatment regime was failing to effect reliable removal of helminth eggs and larvae from six wastewater stabilization ponds. An alternative wastewater treatment regime for the ponds, coupled with a constructed wetland and a fishpond, was devised. Water, soil, and vegetable samples were tested for the presence of helminth larvae and eggs in a time series design over one growing season. From March to August 2014, experimental plots of carrots and Swiss chard were irrigated with wastewater that had been treated by the alternative wastewater treatment regime. It was found that the alternative wastewater treatment regime coupled with the constructed wetland and fishpond appeared to remove helminths completely. No helminths were found in the wastewater after it passed through the alternative system, and none were found in the market-ready carrots and chard. Numbers of helminth larvae and eggs showed evidence of seasonality, which is potentially useful knowledge for farmers in order to avoid helminth infection: almost all larvae were found at the end of the hot dry season. Monsoon rains followed and washed the helminth larvae and eggs away and none were found at the end of the season.